OPTIMALISASI NILAI SIPAKATAU, SIPAKAINGE, DAN SIPAKALEBBI MELALUI PENDEKATAN PSIKOEDUKASI SEBAGAI UPAYA PENCEGAHAN BULLYING PADA SISWA SMAN 1 GOWA - Bustan Bustan; Bahri Bahri; Hasni Hasni; Ahmad Syawaluddin (Jurnal Abdi Negeriku, 2026)
Bullying is a common social problem in schools and affects students' psychological well-being, emotions, and social interactions. This phenomenon also occurs at SMAN 1 Gowa, particularly in the form of verbal and relational bullying. This community service activity aims to enhance the values of Bugis-Makassar local wisdom, namely sipakatau, sipakainge, and sipakalebbi, as a way to prevent bullying through a psychoeducational approach. The implementation method includes several stages: observation and problem identification, program socialization, psychoeducational training, mentoring, and activity evaluation. The program is implemented using methods such as interactive lectures, group discussions, simulations, and role-playing involving both teachers and students. The results of these activities indicate that students increasingly understand the impacts of bullying and are increasingly aware of the importance of fostering social relationships based on mutual respect and appreciation. The internal application of the values of sipakatau, sipakainge, and sipakalebbi also encourages empathy, concern for others, and the courage to remind each other to prevent bullying. In addition, teachers also gained new insights into the importance of integrating local culture into character building within the school environment. This activity demonstrated that strengthening local wisdom through a psychoeducational approach can be an effective prevention strategy in creating a safe, inclusive, and bullying-free school environment.